Теоретико-методичні підходи довизначення сутності інвестиційної діяльності в аграрному секторі - Сітковська, Алла Олександрівна; Sitkovska, Alla; Венгер, О. М.; Venher, O. (Дніпровський державний аграрно-економічний університет, 2023)
У статті розглянуто актуальні питання, які стосуються існуючих підходів до визначення сутності інвестиційноїдіяльності в аграрному секторі. Поглиблено вивчення питань інтенсивності та ефективності інвестиційної діяльності,розглянуто організаційно-економічний механізм відносно специфіки різних регіонів та галузей. Відзначено, що інвестиційна діяльність є надважливою для аграрного сектору, оскільки спрямована не лише на досягнення максимальної ефективності, але й на раціональне використання наявних засобів та ресурсів. Розкрито, що розвиток інвестиційної діяльності є одним із ключових шляхів покращення економічної ситуації держави. Україна має потенційні можливості для збільшення власного виробництва продукції, але для цього необхідні сучасні технології, належна матеріально-технічна база, а отже й в значній мірі інвестиції. Встановлено, що залучення інвестицій в аграрний сектор країни сприятиме нарощуванню виробничого потенціалу галузі, впровадженню інновацій, зміцненню продовольчої безпеки країни та вирішенню значної кількості соціальних потреб населення. Сучасний економічний стан держави вважається нестабільним, тому і постає необхідність систематичної активізації і розвитку інвестиційної діяльності,у тому числі в аграрному секторі економіки.This article proposes to consider current issues related to existing approaches to determining the essence of investment activity in the agricultural sector. During the research, the positions of domestic scientists regarding the relevant direction were analyzed, the legislation of Ukraine was analyzed, and approaches to defining the concepts of "investment activity", "investment attractiveness», «risks", etc. were summarized. Investment activity, its intensity and efficiency, as well as the organizational and economic mechanism have their own specificity for different regions and industries, which requires in-depth study and research of relevant issues. Such activity is extremely important for the agricultural sector, as it is aimed not only at achieving maximum efficiency, but also at the rational use of available means and resources. The development of investment activity is one of the key ways to improve the economic situation of the country. Ukraine has potential opportunities to increase its own production. For this aim, modern technologies, an appropriate material and technical base are needed. Therefore, a large extent requires the attraction of a large amount of investment. It is the attraction of investments in the agricultural sector of the country that will contribute to increasing the production potential of the industry, introducing innovations, strengthening the country's food security and solving a significant number of social needs of the population. Ukraine has a high level of investment potential, but currently does not use it effectively. The current economic state of the country considered as unstable, and therefore there is a need for systematic activation and development of investment activities, including the agrarian sector of the economy. To achieve such goals effectively, it is also worth studying the issue of increasing the industry's investment attractiveness. In turn, increasing the level of investment attractiveness determines a number of operational actions and decisions that should take place in the strategy of economic development. A characteristic feature of investment attractiveness is the continuous movement of the capital invested to different levels of the economy (in the middle of the country or outside its borders) in order to find conditions for obtaining and effective use of such assets .Our country has a great variety of resources (natural, labor), which are extremely necessary for foreign partners, itis extremely attractive for investment in the framework of international cooperation. Therefore, Ukraine faces a key task in the improving implementation of a unified state investment policy. At the same time, it is worth noting that investments are always oriented towards the future and are associated with significant uncertainty of the economic situation. Investment risk, as a component of the process of raising the level of the economy, should be understood as the possibility of not achieving the planned investment goals.
Theoretical and methodological approaches to determining the essence of investment activities in the agricultural sector
Keywords: інвестиції; investment; інвестиційна діяльність; investment activity; інвестиційна привабливість; investment attractiveness; аграрний сектор; agricultural sector; підприємства; enterprises; розвиток; development; ризики; risks